Analysis on the Social Economic Impacts of the Existence of Brondong Nusantara Fishing Port (NFP) Lamongan East Java - Agus Suherman; Adhyaksa Dault (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2009)
Brondong Nusantara Fishing Port (NFP) has a strategic role on the marine and fisheries development, i.e. as a centre of marine fisheries activities, especially for Kabupaten Lamongan east java areas. Brondong NFP is not only as a link between fishermen and the direct and indirect users of the catch, such as traders, processing industries, reatourants etc., but also as an interaction place of coastal community who stays surrounding Brondong NFP. Brondong NFP will become a promising terminal point on land and marine economic activities. The objective of this research was to analyze the social economic impacts of construction and development of Brondong NFP. A study case descriptive survey method was applied. The results showed there was a positive impact, i.e. the increase of efforts acivities and job opportunities for surrounding society, thus, will affect their income. This is because the roles of Brondong NFP as a support system for improving the socialeconomic condition and the welfare of the fishermen.